Performance Analysis of RSA Algorithm Using Elliptic Curve Cryptography, Diffie Hellman And OAEP (International Journal of Engineering and Computer Science, 2017)
Communication is the very important part of any type of network for making it possible to transfer data from one network to another. Communication needs quality and security for better performance which provides confidentiality to users. Cryptographic technique is one of the principal means to protect information security. It is to ensure the information confidential and also provides digital signature, authentication, secret sub-storage, system security and other functions. Therefore, the encryption and decryption solution can ensure the confidentiality of the information, as well as the integrity of information to prevent information from unauthorized access and counterfeiting. Encryption and decryption algorithm’s security is depends on the algorithm and also depends on the key confidentiality. In this paper we compare asymmetric key cryptography algorithm and also implement these algorithm. we compare these algorithm on the basis on time